Assessment of the quality of information support by air radar surveillance systems - Andrusevich, Volodymyr; Obod, Ivan (Національний технічний університет "Харківський політехнічний інститут", 2021)
The paper pays attention to the consideration of the structure of user's information support of the airspace control system at the stage of primary information processing by the joined radar system. This system includes a primary and identification surveillance system, which allows considering the overall structure as a single synchronous network of surveillance information systems. Such a structure can be characterized by an overall integrated quality indicator of the information support of the airspace control system. Such a quality indicator can be the probability of information support, which is the product of the probabilities of correct detection of an air object by the primary radar and identification system on the basis of "friend-foe" and the probability of comparing the coordinate information of primary radar systems and identification systems. This approach allows changing the model of combining information for primary radar systems and identification systems so as to take into account the estimated coordinates of the air object by both information systems due to the weight combination of coordinates of air objects. The calculation of the coordinates of air objects according to the information of the primary radar systems and identification systems allows improving the quality of information support for decision makers in the air traffic control system.

У роботі приділено увагу розгляду структури інформаційного забезпечення користувачів системи контролю повітряного простору на етапі первинної обробки інформації суміщеною радіолокаційною системою. Ця система включає первинну та ідентифікаційну системи спостереження, що дозволяє розглядати загальну структуру, як єдину синхронну мережу інформаційних систем спостереження. Така структура може характеризуватися загальним інтегральним показником якості інформаційного забезпечення системи контролю повітряного простору. Таким показником якості може бути імовірність інформаційного забезпечення, яка є добутком імовірностей правильного виявлення повітряного об’єкту первинним радіолокатором і системою ідентифікації за ознакою «свій-чужий» та імовірності порівняння координатної інформації первинних радіолокаційних систем й ідентифікаційних систем. Такий підхід дозволяє змінити модель поєднання інформації первинних радіолокаційних систем та ідентифікаційних систем так, щоб враховувати оцінені координати повітряного об'єкта обома інформаційними системами за рахунок вагового поєднання координат повітряних об'єктів. Розрахунок координат повітряних об'єктів за інформацією первинних радіолокаційних систем та ідентифікаційних систем дозволяє підвищити якість інфор маційного забезпечення осіб, які приймають рішення в системі контролю використання повітряного простору.
Оцінка якості інформаційного забезпечення радіолокаційними системами спостереження повітряного простору
Keywords: air traffic control system; primary and secondary radar surveillance systems; система контролю повітряного простору; первинні та вторинні радіолокаційні системи спостереження